An Investigation on Teaching Approaches in Teaching English Speaking Skill at Harau Valley English School - Ibrahim, Fajar; Wahyuni, Delvi (Universitas Negeri Padang, 2024)
This study aimed to investigate the teaching approaches used to enhance English speaking skills at Harau Valley English School. This studay was used qualitative research method to gather data through observation and interviews with tutors and students at the school. The analysis used direct approach theory adapted by Bean (2011) and indirect approach theory adapted by Woolfolk (2018). The findings revealed that Harau Valley English School employs teaching approaches that incorporate strategies used in direct approach such as emphasizes clear learning objectives, guided practice, reinforcement and review, and structured lesson plans. This approach ensures a focused learning environment with specific goals communicated to students, active participation in structured activities, and opportunities for consolidation of learning through reinforcement and review activities. In addition, in indirect approach such as Socratic questioning and problem-based learning to empower students in their learning process. These findings highlighted the strengths of various teaching approaches in the context of English language learning. Thus, this study provided valuable insights into effective teaching practices in a specific educational setting and can serve as a basis for the development of improved teaching approaches in the future. These approaches created a dynamic and participatory learning environment at Harau Valley English School. Tutors employ a student-centered approach that not only develops language skills but also nurtures critical thinking, creativity, and practical application of knowledge